2020
DOI: 10.1097/ijg.0000000000001770
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Properties in Primary Open-angle Glaucoma Assessed Through Scheimpflug Corneal Topography and Densitometry

Abstract: The purpose of this study was to compare corneal topography and densitometry measurements in patients with primary open-angle glaucoma (POAG) and healthy subjects.Patients and Methods: A total of 200 eyes of 75 patients with POAG and 125 healthy controls underwent corneal topography and densitometry (Oculus Pentacam HR). The data compared in the 2 groups were: anterior chamber angle, anterior chamber depth, and anterior chamber volume, keratometry (K minimum , K maximum , and K mean ), central corneal thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…They showed that CD had a good diagnostic performance for glaucoma. In the present study, we did not find any differences in CD values of JOAG and control subjects different from a previous study [ 16 ]. This result may be caused by age-related differences of juvenile and older cases.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…They showed that CD had a good diagnostic performance for glaucoma. In the present study, we did not find any differences in CD values of JOAG and control subjects different from a previous study [ 16 ]. This result may be caused by age-related differences of juvenile and older cases.…”
Section: Discussioncontrasting
confidence: 99%
“…In topographic and anterior segment analysis, they found significantly higher central anterior elevation, posterior elevation apex, and anterior chamber angle in eyes with POAG. They also found higher CD values in all depth layers in eyes with POAG than the control eyes and positive correlation between age and CD were also demonstrated in the aforementioned study [ 16 ]. They showed that CD had a good diagnostic performance for glaucoma.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although corneal topography and tomography are widely used, it is common that these technologies are confused [4,6,41,[80][81][82][83][84]. This corrigendum could be associated with the fact that at the time when corneal tomographers were developed, the nomenclature was not yet defined [8].…”
Section: Confusion In Terminologymentioning
confidence: 99%